The politics of social inclusion : bridging knowledge and policies towards social change - Koehler, Gabriele (Ibidem Press, 2020)
This volume looks at concepts and processes of social exclusion and social inclusion. It traces a number of discourses, all of them routed in a relational power analysis, examining them in the context of the UN Agenda for Sustainable Development 2030 with its commitment to "leave no one behind."